Toll-Like Receptor 2 Promoter -196 to -174 Deletion Affects CD4 Levels Along Human Immunodeficiency Virus Infection Progression. (9th June 2020) - Laplana, Marina; Bravo, Maria Jose; Fernández-Fuertes, Marta; Ruiz-Garcia, Celia; Alarcón-Martin, Emilio; Colmenero, Juan de Dios; Caruz, Antonio; Fibla, Joan; Real, Luis Miguel; Royo, Jose Luis
Abstract: Toll-like receptor 2 (TLR2) plays a key role in innate immune response recognizing molecular patterns expressed by pathogens. rs111200466 is a TLR2 promoter insertion/deletion polymorphism with contradictory data about its role in human immunodeficiency virus type 1 (HIV-1) infection. We analyzed rs111200466 in HIV-1 disease progression and showed a correlation with a faster progression to the CD4 + < 200 cells/μL outcome for deletion allele carriers (Cox regression analysis: hazard ratio, 2.4 [95% confidence interval, 1.4–4]; P  = .001). When naive patients with CD4 + < 200 cells/μL started antiretroviral treatment, rs111200466-deletion carriers showed a trend toward a slower, recovery rate (time required to reach CD4 + > 350 cells/μL; Cox P  = .36). Our data suggest rs111200466 as a prognosis factor for HIV-1 disease progression. Abstract : Our results suggest a role of TLR2 germline variants in HIV-1 disease progression rate. Analysis of the TLR2 promoter -196 to -174 deletion links lower levels of TLR2 and diminished CD4 + T-cell counts and worse prognosis, probably due to a lower activation of the immune system.